Effects of ambient air pollution mixtures and household fuel use on progression to advanced cardiovascular-kidney-metabolic syndrome among middle-aged and older adults - Shunchang Fan; Haoyue Hu; Yucheng Li; Ying Deng; Shiao Wang; Juxian Xian; Daoqi Zhu; Minyi Zhang (Ecotoxicology and Environmental Safety)
Background: Cardiovascular-kidney-metabolic (CKM) syndrome is identified as a medical condition with the presence of obesity, diabetes, chronic kidney disease, and cardiovascular disease. This study assesses the associations of ambient air pollution and household fuel usage with the risk of CKM syndrome in advanced stages among middle-aged and older adults. Methods: Data from the China Health and Retirement Longitudinal Study (CHARLS) spanning 2011 and 2015 were used. Data of ambient air pollutants (NO2, SO2, O3, PM1, PM2.5, and PM10) were derived from the ChinaHighAirPollutants (CHAP) dataset. CKM syndrome was separated into five stages (stages 0–4), with stages 3–4 being considered advanced. Logistic regression quantified the separate and joint effects of exposure to ambient air pollution and household fuel usage on advanced CKM syndrome. Multiple ambient air pollutants were evaluated using the weighted quantile sum regression, quantile-based gcomputation, and Bayesian kernel machine regression. Results: In the longitudinal analysis, 18.2 % (604/3317) of participants developed advanced CKM syndrome. For single-pollutant models, ambient air pollutants and household solid fuel use were found as the independent risk factors for advanced CKM syndrome. The highest risk occurred in individuals with combined high ambient air pollution exposure and clean-to-solid fuel use. Additionally, co-exposure to a higher level of ambient air pollutant mixture showed a consistently elevated risk of advanced CKM syndrome, with PM10 being the primary driver. Conclusion: Concurrent exposure to high levels of outdoor and indoor air pollution increases the risk of CKM syndrome in advanced stages.